Sistem Informasi Pelayanan Penerimaan Jasa Tenaga Kerja Berbasis Web (Studi Kasus PT. Defita Bersaudara) - Muhammad Wasil; Hamzan Ahmadi; Baiq. Andriska Candra Permana; Yupi Kuspandi Putra (Infotek: Jurnal Informatika dan Teknologi, 2023)
Technology in this era is developing very rapidly. Especially in the business sector, many companies or agencies use information technology as a means of promotion and information in developing business opportunities, one of which is PT. Defita Bersaudara is a service distribution company engaged in the field of employment abroad. This company distributes Indonesian Migrant Workers Services to several countries such as Malaysia, Singapore, Hong Kong and Taiwan. The system that runs on PT. Defita Bersaudara still uses excel-based data processing in managing and collecting all data on Indonesian workers who depart through PT. defita brothers. This results in the same data being input repeatedly. This information system is capable of providing web-based employment services to make it easier for workers to find information and apply for jobs, applicants do not have to come to the company to register as prospective workers. This application uses the CodeIgniter Framework, so that it can be accessed through internet media by related parties, both the company itself and the wider community in general.